2016
DOI: 10.3892/ijmm.2016.2704
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine suppresses EC9706 cell proliferation and metastasis by upregulating the expression of SOX17 and CDH1

Abstract: 5-Azacytidine is a well-known anticancer drug that is clinically used in the treatment of breast cancer, melanoma and colon cancer. It has been reported that 5-azacytidine suppresses the biological behavior of esophageal cancer cells. However, corresponding mechanisms remain unclear. In this study, using Transwell invasion and cell proliferation assays, we demonstrated that 5-azacytidine significantly inhibited the metastasis and proliferation of EC9706 cells, and upregulated the expression of cadherin 1 (CDH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 15 , 40 42 Among the candidate tumor related new biomarkers, MrgprF, a MAS related GPR family member, was revealed to be downregulated in CM due to the hypermethylation in its promoter region, which could be reversed by 5-Azacytidine treatment, a well-known anti-cancer drug. 43 , 44 Consistently, 5-Azacytidine has previously been shown to behave as an anti-neoplastic agent for B16 melanoma. 45 , 46…”
Section: Discussionmentioning
confidence: 80%
“… 15 , 40 42 Among the candidate tumor related new biomarkers, MrgprF, a MAS related GPR family member, was revealed to be downregulated in CM due to the hypermethylation in its promoter region, which could be reversed by 5-Azacytidine treatment, a well-known anti-cancer drug. 43 , 44 Consistently, 5-Azacytidine has previously been shown to behave as an anti-neoplastic agent for B16 melanoma. 45 , 46…”
Section: Discussionmentioning
confidence: 80%
“…Increased CDH1 expression in cancer cells reduces their ability to undergo epithelial-mesenchymal transition [30] and consequently, their metastatic potential. Interestingly, the expression of CDH1 may be activated by SOX17, as suggested in esophageal cancer cells [31]. In addition, SOX17 is also highly expressed in prostate cancer [32].…”
Section: Discussionmentioning
confidence: 88%
“…In accordance with our study, we observed hypomethylation of DUSP5 in LUAD cells, which resulted in the upregulation of DUSP5 expression. AZA is a well-known, highly effective anticancer medication that is used to treat acute myeloid leukemia, melanoma, breast cancer, and colon cancer [75][76][77][78][79][80]. AZA promotes DNA demethylation by inhibiting DNMTs during replication, inducing silence of gene expression [81,82].…”
Section: Discussionmentioning
confidence: 99%